Illusions of inclusion: Fintech in Africa - Ayodele, Odilile (University of the Witwatersrand, Johannesburg, 2023)
Can fintech deliver on its promise of achieving financial inclusion in Africa? This working paper advances the argument that the heady optimism around fintech is over enthusiastic. It provides an overview of the fintech landscape in southern Africa, focusing specifically on mobile money, which it posits fits more accurately within imaginaries of modernity and inclusion. Employing a mixed methods approach, the paper examines subscription data to highlight that the rural poor are still excluded. Additionally, ignoring the differences between rural and urban locales, including differing social and cultural contexts, exacerbates financial exclusion. The discussion is framed by the emerging concept of digital political economy.
Keywords: African Governance; Digital Age; Digital political economy; Financial inclusion; Fintech; Mobile moeny; SDG-9: Industry, innovation and infrastructure